Exploring the combustion mechanism of single micron-sized aluminum particles with a numerical model - Xinzhe Chen; Jiaxin Liu; Yabei Xu; Di Zhang; Yong Tang; Baolu Shi; Yunchao Feng; Yingchun Wu; Qingzhao Chu; Dongping Chen (FirePhysChem)
In this work, we explore the combustion mechanism of single micron-sized aluminum particles using a numerical model. The Burcat database and Catoire mechanism is considered as the thermodynamic data and the kinetic mechanism for our numerical model of aluminum combustion. Two independent experiments, including particle temperature profiles, ignition delay and burning time, are selected to evaluate the performance of the numerical model. The model shows great agreement for all considered properties. A parametric study is further conducted to identify the effect of involved physical parameters on the combustion process. The diffusion coefficient (D) of oxidizers and the activation energy of surface kinetics (Esurf) and evaporation coefficient (α) of aluminum impact the particle temperature the most. Burning time is most sensitive to the activation energy of surface kinetics (Esurf). The optical measurement in a solid propellant combustion indicates that the contact angle of the oxide cap on Al particle is between 10° and 20°. It is found that the selection of contact angle of the oxide cap significantly impacts the prediction of combustion time and residual of active aluminum. The current work highlights the importance of physical properties on the prediction of Al combustion, suggesting that more detailed evaluation from experiments and theory is encouraged.